2016
DOI: 10.1093/alcalc/agw081
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Alcohol-Flavoured Non-Alcoholic Beverages and Alcohol Use in Japanese Adolescents

Abstract: Consumption of AFNAB is more prevalent among high school students than alcohol consumption and it has a strong association with alcohol consumption. However, concerns that AFNAB use would lead to increased alcohol use were not supported because AFNAB consumption usually started after adolescents began consuming alcohol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Both the consumption of non-alcoholic beer and exposure to the influencer marketing of alcohol have also been positively associated with adolescents' intentions to consume alcohol. Prior studies have established these behavioral patterns in both children and adolescents [40,41]. These findings support the notion that alcohol-free liquor products seem to be marketed to children and adolescents [10,11].…”
Section: Discussionsupporting
confidence: 80%
“…Both the consumption of non-alcoholic beer and exposure to the influencer marketing of alcohol have also been positively associated with adolescents' intentions to consume alcohol. Prior studies have established these behavioral patterns in both children and adolescents [40,41]. These findings support the notion that alcohol-free liquor products seem to be marketed to children and adolescents [10,11].…”
Section: Discussionsupporting
confidence: 80%
“…Conversely, although the voluntary standards concerning AFNABs clearly state that they are to be treated as alcoholic beverages, there is no specification of the advertising time, and almost 30% of the advertisements were aired within the prohibited advertising times for alcoholic beverages. This is worrisome because AFNAB advertisements can tempt adolescents to try alternatives to alcoholic beverages [22]. Therefore, the advertising of AFNABs should be restricted by current advertising time restrictions or banned as a further step.…”
Section: Discussionmentioning
confidence: 99%
“…AFNABs might not be the sole primer for the onset of alcohol use in adolescents, although alcohol and AFNAB use have been significantly associated, and alcohol consumers have substituted AFNABs for alcoholic beverages to meet their needs [22]. The contradiction between the actual marketing message by the industry to sell because of their business goals and the self-regulation guidelines may hinder a clear message to TV viewers, including adolescents and their parents.…”
Section: Introductionmentioning
confidence: 99%
“…Such a decline has taken place at the same time as a general increase in the availability of no-and low-alcohol products [27], which might counter an argument that no-and low-alcohol products act as predominant triggers to consumption of higher strength products by young people. The realist review found one study of young people to test the idea: a Japanese study of over 100,000 adolescents reported that the use of alcohol-flavoured non-alcoholic beverages (AFNAB) usually started after adolescents began consuming alcohol, and not the other way round [92].…”
Section: Academic Publicationsmentioning
confidence: 99%